Nutritional quality of cultured Asian seabass Lates calcarifer in Khulna-Satkhira region of Bangladesh: comparative analysis of two size classes: Nutritional quality of cultured Asian seabass in Khulna-Satkhira region of Bangladesh (Dhaka University Journal of Biological Sciences, 2026)
Asian seabass (Lates calcarifer), locally known as Bhetki or Koral, is a native species to the Indo-Pacific region and is farmed on a small scale in the Southern coastal regions of Bangladesh. This study analyzed the nutritional composition of cultured Asian seabass to identify the nutritionally superior size to aid consumers in making informed choices and to help farmers in determining optimal culture duration. Individuals of two different size classes, (512.06 ± 14.5 g and 1003.5 ± 36.64 g) collected from Khulna and Satkhira districts, were analyzed during this study. The results revealed significant differences (p